Pesan Eskatologis dalam Juz 'Amma: Kajian Hadis Tarbawi atas Refleksi Surat Al-Qari'ah dalam Pembentukan Karakter Muslim di Era Digital - Hikma Apriyani; Zulkifli zulkifli; Ainul Gani; Muhammad Akmansyah; Erjati Abas (IAIN Batusangkar, 2025)
Eschatological studies in Juz 'Amma, particularly reflections on Surah Al-Qari'ah, have profound relevance to the formation of Muslim character in the current digital era. This research aims to explore the eschatological messages contained in Surah Al-Qari'ah using the tarbawi hadith approach, in order to identify Islamic educational values that can shape the character of Muslims with noble morals amidst the rapid development of technology. The method used in this research is a literature study with a qualitative-descriptive approach. Data were obtained from primary sources, namely the Qur'an and Hadith, as well as secondary literature related to Islamic education and Muslim character. The research results show that the eschatological message in Surah Al-Qari'ah contains strong moral values, such as awareness of the afterlife, moral responsibility, and balance between this world and the hereafter. These values can be internalized in the character formation of Muslims in the digital era through the approach of tarbawi hadith, which emphasizes education based on morality and spirituality. By understanding the eschatological message in Surah Al-Qari'ah, Muslims in the digital era can be wiser in utilizing technology and maintaining moral integrity in their daily lives.